Decentralized domestic wastewater treatment using intermittently aerated vertical flow constructed wetlands: Impact of influent strengths. (January 2015) - Wu, Haiming; Fan, Jinlin; Zhang, Jian; Ngo, Huu Hao; Guo, Wenshan; Hu, Zhen; Liang, Shuang
Highlights: Intermittent aeration was effective in COD and TN removal from domestic sewage. Influent strength did not affect pollutant removal in intermittent aerated VFCWs. Removal performance was higher in aerated VFCWs compared with non-aerated VFCWs. Abstract: In this study, the removal performances of organic pollutants and nitrogen in vertical flow constructed wetlands (VFCWs) with and without intermittent aeration fed with different strengths of influent were evaluated as a possible treatment for decentralized domestic wastewater in northern China. The intermittent aeration strategy not only significantly increased removal efficiencies of organic pollutants and ammonium nitrogen (NH4 + -N), but also successfully created alternate aerobic and anaerobic conditions resulting in high total nitrogen (TN) removal. Moreover, increasing influent strength did not affect the removal efficiencies of organic matters and nitrogen in aerated VFCWs. Compared with non-aerated VFCWs, much higher removal of organic pollutants (96%), NH4 + -N (98%), and TN (85%) was obtained simultaneously in intermittent aeration VFCWs, especially at high influent strengths. The results suggest that the intermittent aeration could be an appropriate strategy for achieving the high removal performance in VFCWs, especially for in-situ treatment of high strength decentralized domestic wastewaters.